Poetic prosthetics : trauma and language in contemporary veteran writing / Ron Ben-Tovim. - Ben-Tovim, Ron (Advances in critical military studies., 2023)
'Poetic Prosthetics' provides an analytical tool for reading war and trauma literature, focusing on contemporary British and American soldier writing, published online in various forums by the soldiers themselves since the onset of wars in Iraq and Afghanistan, and in some cases, recent writings of veterans of the Falkland War.